ANALYSIS OF THE IMPACT OF THE IMPLEMENTATION OF SHARIA PRINCIPLES ON THE FINANCIAL PERFORMANCE OF COMPANIES IN INDONESIA - Helma Maraliza (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to investigate how sharia principles are applied has affected Indonesian enterprises' financial performance, particularly in the banking and financial industry. The law of sharia principles applied include the prohibition of usury, gharar, and maysir, as well as the implementation of contracts in accordance with Islamic law. The study's conclusions show that applying sharia principles significantly affects improving the company's financial performance. Companies that implement sharia principles tend to have higher levels of profitability, better financial stability, and more effective risk management compared to conventional companies. These findings support the theory that ethical and transparent sharia principles can improve the competitiveness and sustainability of companies in the long term. This study concludes that the company's financial performance benefits from the application of sharia principles, so it is important for companies in Indonesia to consider implementing these principles as part of their financial strategy.